2022
DOI: 10.3390/diagnostics12122980
|View full text |Cite
|
Sign up to set email alerts
|

Embedded AMIS-Deep Learning with Dialog-Based Object Query System for Multi-Class Tuberculosis Drug Response Classification

Abstract: A person infected with drug-resistant tuberculosis (DR-TB) is the one who does not respond to typical TB treatment. DR-TB necessitates a longer treatment period and a more difficult treatment protocol. In addition, it can spread and infect individuals in the same manner as regular TB, despite the fact that early detection of DR-TB could reduce the cost and length of TB treatment. This study provided a fast and effective classification scheme for the four subtypes of TB: Drug-sensitive tuberculosis (DS-TB), dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…In our suggested model, these three CNN architectures have been uniformly incorporated. It has been demonstrated that the heterogeneous ensemble deep learning model is more effective than the heterogeneous deep learning model at classifying drug-resistant models [ 65 ], which is consistent with our finding that using the proposed model significantly improves solution quality, as shown in Table 2 , Table 3 , Table 4 , Table 5 and Table 6 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our suggested model, these three CNN architectures have been uniformly incorporated. It has been demonstrated that the heterogeneous ensemble deep learning model is more effective than the heterogeneous deep learning model at classifying drug-resistant models [ 65 ], which is consistent with our finding that using the proposed model significantly improves solution quality, as shown in Table 2 , Table 3 , Table 4 , Table 5 and Table 6 .…”
Section: Discussionsupporting
confidence: 90%
“…This study employs UWA, AMIS-WCE, and AMIS-WLCE. The research demonstrated, in accordance with Han et al [ 16 ], Li et al [ 58 ] and Prasitpuriprecha et al [ 65 ], that the AMIS-WLCE improves the solution quality of the existing model.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The artificial multiple intelligence systems (AMIS) method uses a system with many artificial multiple intelligences to assist in the identification of optimal solutions [42,51]. The system is called an intelligence box (IB), and it has algorithms with unique properties.…”
Section: Decision Hybridization Strategymentioning
confidence: 99%
“…Therefore, machine learning was used to forecast the multiobjectives of weld seam properties and remains important when combined with AI for high performance. In [41,42], the authors demonstrated the application of AI using the "unlike entirety model" to categorize types of drug resistance in tuberculosis patients and to identify and classify unsavory images. Application of the unlike entirety AI model for forecasting mechanical properties should provide higher-quality solutions.…”
Section: Introductionmentioning
confidence: 99%